Mixing alcohol with energy drink (AMED) and total alcohol consumption: a systematic review and meta‐analysis. (19th January 2016) - Verster, Joris C.; Benson, Sarah; Johnson, Sean J.; Scholey, Andrew; Alford, Chris
Abstract : It has been suggested that consuming alcohol mixed with energy drink (AMED) may increase total alcohol consumption. Aims of this systematic review and meta‐analysis were (i) to compare alcohol consumption of AMED consumers with alcohol only (AO) consumers (between‐group comparisons), and (ii) to examine if alcohol consumption of AMED consumers differs on AMED and AO occasions (within‐subject comparisons). A literature search identified fourteen studies. Meta‐analyses of between‐group comparisons of N  = 5212 AMED consumers and N  = 12 568 AO consumers revealed that on a typical single drinking episode AMED consumers drink significantly more alcohol than AO consumers ( p  = 0.0001, ES = 0.536, 95%CI: 0.349 to 0.724). Meta‐analyses of within‐subject comparisons among N  = 2871 AMED consumers revealed no significant difference in overall alcohol consumption on a typical drinking episode between AMED and AO occasions ( p  = 0.465, ES = −0.052, 95%CI: −0.192 to 0.088). In conclusion, between‐group comparisons suggest that heavy alcohol consumption is one of the several phenotypical differences between AMED and AO consumers. Within‐subject comparisons revealed, however, that AMED consumption does not increase the total amount of alcohol consumed on a single drinking episode. Copyright © 2016 John Wiley & Sons, Ltd.